Analysis of The Role of The Creative Economy on Society Increasing in Household Income from The Prespective of Islamic Economics (Studies in Society District Pringsewu) - Fatih Fuadi (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2019)
This research is motivated by rural poverty a major problem in the implementation process of development in rural areas, because the majority of poor people living rural areas, the rural development as part of the development. Creative economy is a new economic concept that mix and match information and creativity that relies on ideas, ideas, and knowledge of human resources as a factor of production. There are 14 sub-sectors of the creative industry, one of which is agriculture. Creative economy that is on the village's waringin cider industry refers dragon fruit, dragon fruit farmers who produce the household is an effort to improve the welfare of one of them increase their family income. The problem in this research led to the role of the creative economy in increasing household income through the efforts of dragon fruit cultivation in the village of Sari subdistrict Adiluwih K. Pringsewu district, and the creative economy in increasing household income in the review from the perspective of Islamic economics. Research methods used in this study using qualitative research, using the population of dragon fruit growers 30 plus one vote collectors and village officials as informants. From note analysis can be concluded that based on interviews done by the farmers of dragon fruits in the village of K. Sari subdistrict Adiluwih District Pringsewu., with the creative economy has an important role for farmers, seen from 30 respondents 9 craftsmen increased revenue, 18 stable artisans and craftsmen 3 decreased in the year 2016. Meanwhile, for the study of Islam, the craftsmen have met the production process, marketing market, government policies, economic conditions, the environment and partnership. But does not meet the financial and management indicators were good.